The Effect of Innovation Types on the Performance of Small and Medium-Sized Enterprises in the Sekondi-Takoradi Metropolis - Boachie-Mensah, Francis; Acquah, Innocent S. K. (Archives of Business Research, 2015)
Innovativeness has been touted as one of the fundamental instruments of growth strategies to enter new markets, to increase the existing market share and to provide the company with a competitive edge. Despite this acknowledgement, there is lack of research into how innovation contributes to the performance of small and medium sized enterprises. The aim of this study was to investigate the influence of innovation on organisational performance of small and medium-sized enterprises (SMEs) in the Sekondi-Takoradi metropolis. The research design used was survey research design whilst the research approach was quantitative research approach. Simple random sampling technique was used to collect data from 243 owners/owner managers of SMEs in the Sekondi-Takoradi Metropolis through self-administered questionnaires. Partial least squares (PLS) structural equation modelling (SEM) was used to test the hypotheses postulated. The study revealed that all four different types of innovation significantly influence organisational performance positively, except the product innovation/organisational performance relationship, which was positive but not significant. The results also suggest that innovation accounted for more than fifty one percent of the variation in organisational performance. It was, therefore, recommended that managers of SMEs pay critical attention to the implementation of innovation activities in their firms due to its positive impact of performance. Keywords: Innovation, organisational performance, small and medium-sized enterprises